Foucault’s Political Theologies and the Traces of Liberation Theology in Latin America - Manrique, Carlos A. (Political theology, 2021)
In this piece I explore resonances between Foucault's engagements with political theology and a localized political spirituality embedded in a vast popular uprising in Colombia's Afro-Pacific littoral in May of 2017. I follow the prompt of Foucault's late remarks regarding a “philosophy of the future” that would emerge beyond the frontiers of Europe, attentive to ideas that emerge in people's lived experiences and struggles on the ground; and moved by how life is affirmed otherwise in these practices of resistance. I approach the ethnographic site from this angle, to probe the potentialities and limitations of Foucault's “tactical pointers” for understanding the political force of the popular Catholicism that played a decisive role in this uprising. A form of Christianity that, in the heterogeneous and discontinuous traces of liberation theology in Latin America not only departs drastically from Foucault's characterization of Christianity in his genealogy of moral experience in the West, but also defies in intriguing ways his distinction between “liberation” and “practices of freedom”, and the conceptualization of resistance articulated around it.